KEWENANGAN PENGUJIAN BERKALA KENDARAAN BERMOTOR DI KOTA DENPASAR - Komang Gede Dianaputra; I Wayan Parsa; I Nengah Suharta (Kertha Negara : Journal Ilmu Hukum, 2013)
With the existence of the local autonomy, all sectors which are the implementation are the authority of central government, nowadays that authority to local government. Time have pushs the local gorenment to increase the autonomous execution in a transportation sector hence from as well as the quality. Because of the transfer of the authority from the central govenment to the local government based on local regulation, the issues that will be discussed are how about the authority to the periodic assesment of the vehicles in Denpasar city, after the enactmen of the local regulation of Denpasar city, and what are the obstacles in the implementation of the vehicles assesment in Denpasar city. The method which is used is the normative legal method. Concerning the authority of the Denpasar city in the periodic assesment of the vehicles are already enacted in the local regulation of Denpasar city. That also the same for the obstacles, which are persounels, equipments and also the find that already tried to solve by the government.